Effect of load and pulling speed on the static coefficient of friction of cross-country skis on snow - Quirion Cantin, N.; Lépine, J.; Bégin-Drolet, A. (Sports Engineering, 2024)
This study examines the effective static coefficient of friction of cross-country skis on snow, using an on-site linear tribometer. Friction is a critical factor influencing ski performance and athlete competitiveness. This research investigates the effects of varying loads and pulling speeds on the static coefficient of friction under actual snow conditions. A specialized measuring system and protocol were designed and tested, ensuring an accurate and reliable assessment of the static coefficient of friction. The tribometer can be used on a cross-country ski racetrack, providing measurements that reflect real-world racing conditions. This approach ensures that the findings are relevant and applicable to competitive skiing scenarios. The results show an increase in the effective static coefficient of friction with both higher loads and speeds, highlighting the complex interaction between ski, wax, and snow. These findings provide insights for selecting ski and wax combinations, offering a measurable approach that reduces reliance on subjective methods.